A 2-Mb YAC contig encompassing three loci (DXF34, DXS14, and DXS390) that lie between Xp11.2 translocation breakpoints associated with incontinentia pigmenti type 1. - Reed, V; Rider, S; Maslen, G; Hatchwell, E; Blair, H; Uwechue, I; Craig, I; Laval, S; Monaco, A; Boyd, Y (1994)
We demonstrate that all the repeat elements representing the conserved loci DXF34 and DXS390 lie between the X;9 and the X;17 translocation breakpoints associated with incontinentia pigmenti type 1 (IP1). Sequence-tagged sites (STSs) at DXF34S1, DXS14, and DXS390 have been used to isolate YAC clones containing these loci, and a contig of approximately 2 Mb has been constructed. Patterns of hybridization observed in the YAC clones indicate that DXS390 comprises two distinct regions (A and B). The STS at DXS390 detects the A region and includes a polymorphic CA repeat (PIC = 0.25). This expansion of the cloned region around DXF34 and DXS390 will enable the isolation of additional conserved sequences that will help in understanding both the lesions underlying the pathogenesis of IP1 and the size and extent of the man-mouse homologous block defined by DXF34.